Methodology for the Development of Step/Express Applications in the Area of Process Plannin - Neaga, Irina; Kuric, Ivan (Communications - Scientific letters of the University of Zilina, 2000)
The paper deals with the research related to the development of a generic methodology which enables the interaction of STEP/EXPRESS based models, and tools for specific applications in the area of process planning.